2022
DOI: 10.31594/commagene.1204178
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of The Effect of Thymbra capitata Ethanolic Extract on Galleria mellonella Hemolymph Antioxidant Enzymes

Abstract: Conehead thyme (Thymbra capitata) is widely distributed in the countries of the Mediterranean region and used due to its medical properties. The antibacterial, antifungal, and strong antioxidant properties of T. capitata are known. The model organism Galleria mellonella is mostly preferred for immunological studies and for the study of human pathogens. The aim of the study was to determine the effect of the ethanolic extract of T. capitata on the antioxidant defense of the hemolymph in G. mellonella larva. Sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These studies indicate that plant growth regulators and secondary metabolites reduce antioxidant enzyme activity at high doses. According to a study with Tymbra capitata extract, the extract reduced SOD and CAT activity in G. mellonella hemolymph ( Kaya, 2022 ). The results of our study showed that the P. major extract did not cause a significant change in the CAT activity and MDA amount at high doses compared to the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies indicate that plant growth regulators and secondary metabolites reduce antioxidant enzyme activity at high doses. According to a study with Tymbra capitata extract, the extract reduced SOD and CAT activity in G. mellonella hemolymph ( Kaya, 2022 ). The results of our study showed that the P. major extract did not cause a significant change in the CAT activity and MDA amount at high doses compared to the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the method of Kaya (2022) was used. All test readings were made in the microplate reader at the appropriate wavelengths and on the microplates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were carried out according to the methods specified in [37]. According to this, the [41] method for determination of total protein, [42] for determining of SOD activity, [43] for CAT activity and [44] methods for MDA levels were adapted and used.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…Furthermore, G. mellonella has the ability to endure a range of temperatures (25-37 °C) that are conducive to conducting infection studies, and this characteristic enables researchers to carry out experiments that closely resemble those conducted in mammalian systems [31]. There are many studies on G. mellonella hemolymph antioxidant enzymes and these studies show that G. mellonella hemolymph antioxidant enzymes are affected by plant extracts and other different substances [32][33][34][35][36][37]. Based on the results of studies investigating the effects of olive leaf extract on G. mellonella cell-mediated immunity [38] and phenoloxidase (PO) activity [39], it was observed that the administration of olive leaf extract at low doses led to a notable increase in cellular immune responses.…”
Section: Introductionmentioning
confidence: 99%